Formação do rendimento de grãos de soja em função de arranjos de plantas, genótipos e épocas de semeadura - Chaves, Adilar (2012)
The spatial distribution of plants in the field interferes directly in the growth, branching, dry matter production and grain yield in soybean. The arrangement that provides greater yield varies according to genotype and sowing date. Genotypes recently become available for use have short cycle and indeterminate growth habit, which differ from the traditionally grown in the Rio Grande do Sul State, with medium maturity and determinate growth habit. The objective of this study was to characterize the effect of plant spacings and sowing dates on the distribution of yield components and distribution of dry matter in stems, branches in the R5 stage and at harvest, in genotypes with different growth habits. In season growth 2009/2010 were evaluated two rows spacing (34 and 50 cm), five populations (100, 170, 240, 310 and 380 000 thousand plants ha-1) in two soybean genotypes of indeterminate growth ("NS 4823 RR" and "NA 5909 RG") in two sowing dates (28/10 and 15/12), in Sertão/RS. In season growth 2010/2011 were evaluated two sowing dates (12/11 and 14/12), four genotypes ("NS 4823 RR", "NA 5909 RG", "A 6411 RG" and "BR SUL LA" the last two, with determinate growth habit) and five plant populations (100, 170, 240, 310 and 380 thousand plants ha-1) at 50 cm spacing between rows in Passo Fundo/RS. The contribution of the vertical middle third of the plant varied little between the arrangements and sowing dates, while the reduced basal third of upper and increased from October to December, in the genotype "NA 5909 RG" more than "NS 4823 RR". The number of reproductive nodes per area increased linearly with increasing population. The number of pods and grains per plant and per area was proportional to the number of reproductive nodes, with little trade-off between plant population and vegetables per node. The weight of 100 grains produced in the stem varied more than of 100 grains produced in the branches depending on the sowing dates and plant populations. Highest yields were obtained with sowing in November and the lowest yield occurred in the late sowing with lower plant populations. The yield differences due to sowing dates and plant spacings are mainly due to branching resulting in each genotype, with little change in yield components located in the stem and vary according to genotype more than the habit of growth